A New Ritodrine Selective Electrode and its Pharmaceutical Application - Reda Ammar (E-Journal of Chemistry)
A novel ritodrine hydrochloride ion-selective PVC membrane electrode based on ion-pair complex of ritodrine-tetra phenyl borate was prepared with di-n-butyl phosphate as a plasticizer. The influences of membrane composition, temperature, pH of the test solution and foreign ions on the electrode performance were investigated. The electrode showed a Nernstian response over a wide ritodrine concentration range (1×10−5- 1×10−2 M) with a slope of 59.33 mV decade−1 and was found to be very selective, precise and usable within the pH range 3-7.5. The standard electrode potentials, E°, were determined at different temperatures and used to calculate the isothermal temperature coefficient (dE°/dT) of the electrode, which was 0.00075. The electrode was successfully used for potentiometric determination of ritodrine hydrochloride both in pure solutions and in pharmaceutical preparations.